Development of Interactive E-Module Based on CLO3D for Kebaya Kutubaru Modifications as a Preparation for Garment Creation - Annisa Sholikhatul Fatih; Sri Endah Wahyuningsih (Universitas Negeri Semarang, 2026)
The utilization of three-dimensional fashion design technology in vocational learning at vocational high schools is still suboptimal, particularly in providing structured digital learning materials that support independent practical learning. This condition affects the mastery of digital fashion design skills among students. This study aims to develop an interactive e-module based on digital fashion design applications for the topic of Preparation for Kebaya Kutubaru Modification and to assess its feasibility, practicality, and effectiveness as a learning medium. This research employs the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consist of 18 students from the 11th grade of Fashion Design Expertise Program at SMK Ibu Kartini Semarang. Data collection techniques include expert assessments, user response questionnaires, and pre- and post-performance tests. The results of the study indicate that the developed e-module is categorized as very feasible and highly practical for use in learning. Furthermore, the analysis shows an improvement in the skills of the students after using the e-module, with the N-Gain value categorized as moderate. Therefore, the developed interactive e-module is deemed effective as a learning medium to support the enhancement of digital fashion design skills among SMK students.